Assessing the Pharmacological and Therapeutic Efficacy of Traditional Chinese Medicine Liangxue Tongyu Prescription for Intracerebral Hemorrhagic Stroke in Neurological Disease Models - Li, Xun; Huang, Xi; Tang, Yuanlin; Zhao, Fangli; Cao, Yanmei; Yin, Lian; Li, Guochun (Frontiers in Pharmacology, 2018)
Intracerebral hemorrhage (ICH) is a fatal subtype of stroke, with crucial impact on public health. Surgical removal of the hematoma as an early-stage treatment for ICH can’t improve long-term prognosis remarkably. Liangxue Tongyu Prescription (LP), a traditional Chinese medicine formula, includes eight ingredients and has been used to treat ICH in the clinical. In the study, we elucidated the pharmacological efficacy and therapeutic efficacy of LP to dissect the mechanism of LP against ICH via network analysis and experimental vali-dation. First, we discovered 34 potential compounds and 146 corresponding targets in LP based on network prediction. 24 signal pathways were obtained by the Clue Go assay based on potential compounds in LP against ICH. Second, we found that LP can not only decreased the level of HS-CRP, TNF-α, NF-kβ, D2D, E2, S-100B, NSE and IL-1 in plasma on sponta-neously hypertensive rats, but also promoted cell proliferation and inhibited cell apoptosis on the glutamate-induced PC12 cell.The compounds including Taurine, Paeonol and Ginsenoside Rb1 in LP can activate PI3K/AKT pathway. Third, From the three-factor two-level factorial design, compound combinations in LP, such as Taurine and Paeonol, Taurine and Geniposide, Ginsenoside Rg1 and Ginsenoside Rb1, had first-level interactions on cell proliferation. Compound combinations including Taurine and Paeonol, Ginsenoside Rg1 and Ginsenoside Rb1 had a s significant increase in efficiency on inhibiting the apoptosis of PC12 cells at the low concentration and up-regulating of PI3K and AKT. Overall, our re-sults suggested that LP had integrated therapeutic effect on ICH due to activities of an-ti-inflammatory, anti-coagulation, blood vessel protection and protection neuron from excitotoxicity based on the way of “multi-component, multi-target, multi-pathway”, andcompound combination in LP can offer protection neuron from excitotoxicity at the low concentration by activation of the PI3K/Akt signal pathway.